Electromagnetic radiation towards adult human head from 900MHz handheld mobile phone - Mat, D.A.A.; Franky, W.T.; Kipli, K.; Joseph, A.; Sahrani, S.; Lias, K.; Suhaili, S. (IEEE, 2010)
Electromagnetic radiation produce by mobile phone and the relationship with the human's health is not a new issue nowadays. Since the used of mobile phone had increased rapidly over the past few years, people are becoming more concern with their health when dealing with the so-called electromagnetic radiation. This type of radiation would leads to heating of body tissue at specific rate called the thermal radiation. Thermal radiation depends on the frequency of the energy, the power density of the radio frequency field that strikes the body and the polarization of wave. This paper will discuss on the result collected from the thermal radiation generated by handheld mobile phone with frequency of 900 MHz towards adult human head. The analysis is conducted in a laboratory with average of 45 minutes talking hour with two different types of mobile phone, internal and external antenna. The results show an increased of heat especially at the place near the ear skull after 45 minutes of operation. When comparing both different types of mobile phone, mobile phone with external antenna produce more heat compared to mobile phone with internal antenna.